PENGEMBANGAN MODUL BERBASIS SCAN BARCODE SEBAGAI MEDIA PEMBELAJARAN PADA MATERI BAGIAN TUMBUHAN DAN FUNGSINYA (Kelas IV UPT SD Negeri Resapombo 05 Kecamatan Doko Kabupaten Blitar) - Sindi Ratika; Mohamad Fatih; Cindya Alfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The availability of adequate learning media can facilitate the teaching and learning process effectively and efficiently. The provision of media and the application of dynamic, conducive, and interactive learning methods are very important to optimize the development of students' potential. Many fourth grade students still have difficulty fully understanding the content delivered by their teachers. As a result, some students are less active because they are less interested in the material. Through the use of media in the form of barcode scan-based modules, researchers provide solutions that help teachers incorporate technology into the teaching and learning process, including the use of mobile phones. The Research and Development (R&D) approach was used in this study. The ADDIE model is used to describe the phases involved in implementing research and development activities. This stage includes analysis, design, development, implementation, and assessment. Data collection in this study was carried out using interview and questionnaire techniques. The validity of the material expert media was 67%, media experts were 92%. language experts were 78%. thus, this module can be used without the need for major revisions. The practicality of this barcode scan-based module was assessed by a grade IV teacher at UPT SD Negeri Resapombo 05, Doko District, Blitar Regency, with a percentage result of 80%, student evaluations showed that the image & color display received the highest score (88%), followed by aspects of instructions, language, and time allocation which each received 86%. Meanwhile, the material aspect received a score of 84%, which indicates that there is room for improvement in the presentation of content.